Unusual endosteally formed bone tissue in a patagonian basal Sauropodomorph dinosaur - Cerda, Ignacio Alejandro (2014)
Mussaurus patagonicus (Dinosauria: Sauropodomorpha) is a basal sauropodomorph from the Late Triassic of southern Argentina that is known from a large number of individuals, including juveniles, subadults, and adults. Here, we report on the occurrence of an unusual bone tissue in an individual of M. patagonicus. The rather atypical bone tissue is located within the femoral medullary cavity and also occurs within several erosion cavities of the midinner part of the cortex. This tissue is well vas- cularized and is composed of a matrix that consists of abundant and densely packed osteocyte lacunae. Although some features of this tissue resembles avian medullary bone, the histological features are distinctive and share more features with the pathological, reactive bone produced in extant birds in response to a retrovirus-induced disease (avian osteopetro- sis). Here, we also discuss and provide histological features to effectively differentiate endosteally formed medullary bone from pathological avian osteopetrosis.